Audience's Meaning of Marriage Procession in "Atta and Aurel's Love Bond" Show - Mitha Adilina; Nur Maghfirah Aesthetika (Indonesian Journal of Cultural and Community Development, 2022)
The phenomenon of artist marriages being broadcast live on television is now becoming more and more common. Television is one form of mass communication technology development that many people choose so that viewers can now get all the information they need in a simple way. With so many broadcasts on television, researchers are interested in discussing the audience's meaning of one of the most widely discussed shows, namely the wedding broadcast of a pair of public figures in the event "Ikatan Cinta Atta and Aurel" broadcast by RCTI. Therefore, the researcher wants to know how the audience's acceptance of wedding shows and the diversity of wedding culture in Indonesia in the "Atta and Aurel Love Association" event. The researcher used the reception analysis method with a qualitative research approach which was carried out by in-depth interviews with ten informants in Entalsewu Village RW 04 Buduran Sidoarjo. In selecting the informants, the researcher used purposive sampling technique. The result of this research is the audience's meaning which is classified into three positions, namely Dominant Position, Negotiated Position and Optional Position. there are seven informants who are included in the Dominant Position, then there are two informants who are included in the Negotiated Position, and finally there is one person who is included in the Optional Position.